Water Qualities and Sediment Qualities in the Offshore Shellfish Culture Areas in Sriracha District, Chonburi Province - Buranapratheprat, Anukul; Kongpradit , Pattinee (Burapha Science Journal, 2026)
Water and sediment qualities in shellfish culture areas off the coast of Sriracha were investigated in October 2021 (inter-monsoon), January 2022 (northeast monsoon), May 2022 (inter-monsoon), and August 2022 (southwest monsoon). This study aims to monitor the overall environment around offshore shellfish culture areas in Sriracha and comprehend this effect. It was found that the general water qualities were within the standard for coastal aquaculture, except dissolved oxygen was below the threshold in October 2022 and May 2022. The average values of ammonia, nitrite, nitrate, orthophosphate, and silicate were 39.54±30.71 µg-N/L,11.54±10.74 µg-N/L, 12.86±11.46 µg-N/L, 21.41±11.78 µg-P/L, and 595.92±307.29 µg-Si/L, respectively. In October 2021, the concentrations of nitrite, orthophosphate, and silicate were highest in all observation periods. In May 2022, the highest levels of ammonia and nitrate were found. Silicate was high in all study periods caused by freshwater runoff and resuspension of the sediment along the coast. The nutrients in seawater increased by shellfish culture itself and from external sources by water inlet from Sukreep Canal and the south of the culture area. The organic matter was accumulated in the north of Koh Loy. Most of the sediment particles in the shellfish culture area were coarse sand that were larger than those in the areas without shellfish culture. Water content and total organic matter in the sediments were not significantly different from the surrounding area. This is due to the rapid rate of decomposition of organic matter and the good water exchange.